Tensile and Flexural Strength Fiberglass Mixed Green Mussel Shell Powder for Fishing Vessel Size below 5 GT - Paska, Adhi; Yusrizal, Yusrizal; Hermawan, Maman; Idnillah, Mochamad (Journal La Lifesci, 2025)
Green mussel (Perna viridis) is a marine organism that is widely cultivated and considered a leading commodity in the fisheries sector. The increase in mussel production has resulted in a significant amount of shell waste. Improperly managed mussel shell waste can have a negative impact on the environment. However, green mussel shell waste has great potential for reuse, one of which is as a composite material in fiberglass manufacturing. The high calcium content in mussel shells can serve as an additional reinforcement in fiberglass composites. The wood crisis as a raw material for boat construction, which also contributes to environmental deforestation, has led to the consideration of alternative materials such as fiberglass for boat building. This research is an experimental study on the utilization of green mussel shell (GMS) waste as a fiberglass mixture material for boat construction. An ideal composition between the GMS waste powder and fiberglass material is expected to enhance the mechanical strength of fiberglass fishing boats. The study shows that the addition of 20% GMS powder in fiberglass lamination improves mechanical properties, with a maximum tensile stress value of 113.23 MPa. Meanwhile, the maximum flexural strength is observed at 15% GMS powder composition, reaching 192.38 MPa. The addition of GMS powder has the potential to strengthen fiberglass, making it suitable for applications such as fishing boat hulls. However, adding more than 30% GMS powder decreases the material’s strength, particularly in tensile testing. Further research is needed to explore the use of GMS powder for waste reduction and to provide insights into its applications in fiberglass boat manufacturing.